Problems and stakeholder responsibilities in island tourism : the case of Tioman Island in Malaysia - Ho, Jo Ann; Chia, Kei Wei; Ng, Siew Imm; Ramachandran, Sridar (Sage Publications, 2017)
Tioman Island in Malaysia was once voted one of the most beautiful islands in the world. However, this ranking has gradually slipped, due to development and poor environmental management of the island. The authors employ the stakeholder theory in examining the perceptions of four stakeholder groups (tourists, local residents, government agencies, and business operators) on the environmental problems faced on the island and to identify the parties jointly responsible for solving these problems. A total of 15 problems were identified from 46 exploratory interviews conducted prior to the questionnaire survey. A questionnaire was constructed based on the interview data, and 320 questionnaires were collected from the four stakeholder groups. The results provide support that different stakeholder groups identify different problems and they perceived responsibility for solving these problems. The findings also indicated that problems related to limited road access, neglect of local community, limited phone and internet access, and dirty beaches needed immediate attention.